Measurements of Lα, Lβ, Lγ and M X-ray production cross sections of Os, Ir and Pt by low-energy electron impact: Comparisons of experiment with theory. (May 2017) - Zhao, J.L.; An, Z.; Zhu, J.J.; Tan, W.J.; Liu, M.T.
Abstract: Experimental determinations of Lα, Lβ, Lγ and M X-ray production cross sections and their ratios for Os (Z=76), Ir (Z=77) and Pt (Z=78) by electron impact at incident energies of 6–30 keV are presented. Thin films of the studied elements deposited on thick carbon substrates were employed as targets in the experiments. Enhancements in L- and M-shell characteristic X-ray production due to electron-scattering effects in the double-layer structure target were corrected by means of Monte Carlo simulations. Comparisons were made between the measured Lα, Lβ, Lγ and M X-ray production cross sections and their ratios with the DWBA and PWBA-C-Ex theories and with other experimental data in the literature. In the case of L-subshells, the measured data of Os and Pt agree well with the theoretical values within the experimental uncertainties, but appreciable discrepancies between the experiment and theory exist for Ir; in the case of the M-shell, measured data for Ir show good agreement with theoretical values within the experimental uncertainties, but the measured results are somewhat lower than the theoretical values for Os and Pt. Finally, possible factors that could affect the comparisons between experiment and theory on cross-section ratios are discussed. Highlights: We measured L and M shell X-ray production cross sections of Os, Ir and Pt. Corrections for effects of target substrates are made by Monte Carlo simulations. Measured L and M shell X-ray production cross sections are compared with theories.